The Use of Equine-Assisted Therapy in Patients With Aggression and Agitation Behaviors due to Moderate-to-Severe Dementia: A Case Series - Beatriz Pozuelo Moyano; Jean Pierre Schuster; Kevin Swierkosz-Lenart; Leonardo Zullo; Charline Compagne; Caroline Imobersteg; Armin von Gunten; Pierre Vandel (Case Reports in Psychiatry)
Behavioral and psychological symptoms of dementia (BPSD) are very common, and their management remains challenging. In older people with dementia, equine-assisted therapy (EAT) may be a promising nonpharmacological intervention for the management of BPSD. Here, we present five cases of patients with agitation and aggression due to moderate-to-severe dementia. They had overall two to three sessions of EAT at a frequency of one session per week. We assessed the Neuropsychiatric Inventory Questionnaire (NPI-Q) score before and 1 day after the second EAT session. We observed a discrete reduction in the NPI-Q after the EAT sessions, although not all of the improvements experienced by patients, families, and carers were reflected in the NPI-Q. Future studies should be conducted to assess subjective lived experiences of EAT in patients with moderate-to-severe dementia.